VIBRATION RESPONSE MEASUREMENT ON SHAKING TABLE AND ITS SIMULATION USING MSC NASTRAN 4.5 - SETIYONO (NIM : 131 05 014); Pembimbing : Prof. Dr. Ir. Komang Bagiasna, AMRIH
Finite element method (FEM) can be used to evaluate a complex mechanical structure. Finite element method is a numerical method to approximate analytical solution. This research use MSC Nastran 4.5 as FEM software. A normal modes analysis is conducted to the developed finite element model and the results are validated by measuring the mechanical structure Frequency Response Function (FRF). Based on valid finite element model, vibration response of the finite element model due to seismic excitation is evaluated using frequency/harmonic response analysis that already available in this software. The results are compared to the mechanical structure vibration responses which are measured experimentally using shaking table as excitation source. The result of this research indicates that FEM vibration response has a different value with the experimentally vibration response. The comparation between FEM vibration response and experimentally vibration response is defined as scaling factor. The value of scaling factor is 2 and constant relatively across a range of excitation frequencies. That phenomenon concludes that scaling factor can be used as a calibration factor to predict the mechanical structure vibration response.